A study on the information needs and information-seeking behavior of rural women in Northern Samar - Ortego, Shealtiel Wahini P.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2018)
Information plays an important role in every human activity, and if used properly, could bring about development and change in an individual’s life and in the society. This explains why access to information among all people regardless of socioeconomic and cultural background should be promoted. It bears stressing that people belonging to the disadvantaged sectors of the society such as ethnic minorities and rural dwellers are particularly susceptible to disparities in accessing information.

Hence, information services should be provided and brought closer to these underserved sectors of the society. The most practical and feasible way to do so is to tailor-fit information services to the communities’ information needs and base it on their information-seeking behavior. This study is conducted along this vein. Specifically, this study sought to determine the information needs and information-seeking behavior, along with the inquiry into the challenges that the rural women of Northern Samar are facing in finding the information that they need.

This study utilized the qualitative research paradigm, with focus group discussions as the main method for the collection of data. In general, the findings of the study revealed that because of their societal roles mainly as mothers and household managers, which is evident in most of the participants, the nature of the information they seek directly tied to such roles. The information they require is typically about preventive health care, housekeeping and household maintenance, as well as financial or economic information, which are all oriented towards the welfare of their respective families. Additionally, socio-economic and environmental factors proved to have an influence on the information needs of the women as manifested in their information requirements about disaster and economic/ occupation-related matters.

With regards to the nature of the information sources that the participants consult, it revealed that interpersonal sources were preferred by a majority of them, and such preference could be explained by the Principle of Least Effort (PLE). In addition, media sources such as television and radio also proved to be important information sources for them as these are cheap and are in fact, widely available among the rural households. Moreover, with regard to health information, rural health centers and barangay health workers are also considered to be credible sources by some, but most women prefer informal sources such as friends and family. Lastly, formal sources proved to be the least preferred and least consulted sources of information among the said population.

The challenges in seeking information among the respondent rural women were found to be associated with their surrounding circumstances such as their role as home managers which limits or worst, takes away their time that is supposedly to be spent in seeking for information. Socio-cultural and environmental factors were also revealed to have bring forth constraints on their information-seeking. Moreover, the inaccessibility of information centers and the lack thereof have also an impact on the information-seeking of the rural women under study.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information-seeking behavior -- Women; Information needs -- Women; Information behavior